2010
DOI: 10.1149/1.3484095
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation in Anodic Aluminum Oxide Growth by Flow Instability and Dynamic Restabilization

Abstract: The viscous flow of oxide driven by the electrostriction force during the growth of anodic aluminum oxide is treated by linear stability and scale analysis. A uniform oxide film is unstable to a periodic deformation. The restabilization of pore growth is examined by scale analysis of the steady pore diameter. The pattern spatial period and pore radius predicted by the analysis are compared with experimental observations reported in the literature.Anodizing is an electrochemical process technology that imparts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
(25 reference statements)
2
27
0
Order By: Relevance
“…Thus, peaks would grow and valleys deepen. A flow instability mechanism of porous anodic oxide formation was also presented by Barkey and McHugh [27]; however, flow in their model was driven by electrostriction stress, which according to our experiments is small compared to the oxide stress [21].…”
Section: Oxide Morphology Evolutionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, peaks would grow and valleys deepen. A flow instability mechanism of porous anodic oxide formation was also presented by Barkey and McHugh [27]; however, flow in their model was driven by electrostriction stress, which according to our experiments is small compared to the oxide stress [21].…”
Section: Oxide Morphology Evolutionsupporting
confidence: 72%
“…Thus, stress-driven ionic transport toward the pore walls is envisioned to assist pore formation. Various investigators have suggested transport mechanisms by elastic displacement [22][23][24], stress-affected ion migration [8], or oxide flow [16,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Their calculations revealed increasingly tensile stress at higher anodizing current density, consistent with some but not all experiments [114]. The morphological instability study by Barkey and McHugh incorporated bulk oxide motion as an essential feature of the instability mechanism driving pattern formation [113]. This model treated oxide motion as Newtonian viscous flow generated by electrostriction stress at the oxide-solution interface.…”
Section: Bulk Motion Of Oxidementioning
confidence: 53%
“…Such motion has been interpreted differently as either plastic flow, or rigid body motion due to elastic forces [53,64,73]. In mathematical models, oxide motion has been treated as viscous flow [65,87,113]. Houser and Hebert tested the interpretation of bulk oxide motion as plastic flow, in a simulation of steady-state growth of porous anodic alumina [65].…”
Section: Bulk Motion Of Oxidementioning
confidence: 99%
See 1 more Smart Citation